2011
DOI: 10.1644/10-mamm-a-393.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom patterns of roost emergence in big brown bats,Eptesicus fuscus

Abstract: In most colonial species of bats individuals emerge en masse from day roosts each evening to begin foraging. Although some aspects of emergence behavior are understood, one previously unexplored area is the specific order in which individuals emerge. The goal of our research was to determine if big brown bats, Eptesicus fuscus, fitted with passive integrated transponder tags emerge from roosts in buildings each evening in a nonrandom order. We assessed relative and absolute order of emergence to determine if o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although there are additional reasons for group living [18] , [51] , our model illustrates the links between the environment (proportion of suitable trees), cognitive skills and the colony size of bats. In our model we did not consider other strategies of information transfer, such as following behaviour, which could further increase the effectiveness of roost finding [13] , [52] , [78] , [79] . Nevertheless, even with our conservative approach utilising the simplest mechanism for information transfer, the results show advantages of living in groups under specific circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are additional reasons for group living [18] , [51] , our model illustrates the links between the environment (proportion of suitable trees), cognitive skills and the colony size of bats. In our model we did not consider other strategies of information transfer, such as following behaviour, which could further increase the effectiveness of roost finding [13] , [52] , [78] , [79] . Nevertheless, even with our conservative approach utilising the simplest mechanism for information transfer, the results show advantages of living in groups under specific circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Clustered emergence of bats from a roost may constitute an antipredator behavior (Speakman et al 1995), yet clustered emergence may be disrupted in large colonies due to bottleneck effects (Speakman et al 1999). Gillam et al (2011) found non-random patterns when pit-tagged Eptesicus fuscus emerged from buildings, indicating that these bats may form social bonds that likely influence their foraging. Information transfer might also be involved during swarming at buildings as observed in some temperate zone bats (Kanuch et al 2010;Šuba et al 2010).…”
Section: Reduced Predation Riskmentioning
confidence: 96%
“…In turn, field experiments help validate laboratory observations. For example, given territorial behaviors and roost-exiting patterns exhibited by these bats in the wild ( Gillam et al, 2011 ) as well as anecdotal laboratory evidence, it is expected that big brown bats form hierarchical colonies, and we are only starting to study this systematically. This type of reciprocal studies will add to the knowledge of big brown bat ecology that may inform future conservation efforts for this species.…”
Section: Discussionmentioning
confidence: 99%